2003
DOI: 10.1159/000070928
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effect of Air Pollution on Respiratory Complaints, Exhaled NO and Biomarkers in Nasal Lavages of Allergic Children during the Pollen Season

Abstract: During 2 months of the pollen season, the acute and putative adjuvant effect of traffic-related air pollution on respiratory health was investigated in children sensitised to grass pollen or house dust mite (HDM). Respiratory complaints were objectified via measurement of exhaled NO and inflammatory mediators in nasal lavage (NAL). During the study children, skin prick negative (n = 31) or positive to grass pollen (n = 22), HDM (n = 34) or grass pollen + HDM (n = 32), kept a daily diary on respiratory symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 41 publications
2
41
0
1
Order By: Relevance
“…As a result, FeNO is generally considered to be a reliable noninvasive marker of airway inflammation. Exhaled nitric oxide was used as a biomarker in numerous studies to evaluate the effects of air pollution (Adamkiewicz et al, 2004;BarrazaVillarreal et al, 2008;Delfino et al, 2006;Fischer et al, 2002;Franklin et al, 2000;Giroux et al, 2001;Holguin et al, 2007;Jansen et al, 2005;Koenig et al, 2003Koenig et al, , 2005Mar et al, 2005;Nickmilder et al, 2003;Steerenberg et al, 1999Steerenberg et al, , 2001Steerenberg et al, , 2003Van Amsterdam et al, 1999a, 1999b. Results of these studies supported the idea that outdoor air pollution may lead to airway inflammation (Holguin, 2008).…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…As a result, FeNO is generally considered to be a reliable noninvasive marker of airway inflammation. Exhaled nitric oxide was used as a biomarker in numerous studies to evaluate the effects of air pollution (Adamkiewicz et al, 2004;BarrazaVillarreal et al, 2008;Delfino et al, 2006;Fischer et al, 2002;Franklin et al, 2000;Giroux et al, 2001;Holguin et al, 2007;Jansen et al, 2005;Koenig et al, 2003Koenig et al, , 2005Mar et al, 2005;Nickmilder et al, 2003;Steerenberg et al, 1999Steerenberg et al, , 2001Steerenberg et al, , 2003Van Amsterdam et al, 1999a, 1999b. Results of these studies supported the idea that outdoor air pollution may lead to airway inflammation (Holguin, 2008).…”
mentioning
confidence: 78%
“…Previously, FeNO-correlated exposure to fine particles was assessed outdoors by fixed stations (Adamkiewicz et al, 2004;Barraza-Villarreal et al, 2008;Delfino et al, 2006;Jansen et al, 2005;Mar et al, 2005;Steerenberg et al, 2001Steerenberg et al, , 2003Van Amsterdam et al, 1999a) or through objective assessments at the community level Koenig et al, 2003Koenig et al, , 2005 or in indoor environments Koenig et al, 2003Koenig et al, , 2005. Only three recent studies found significant associations between FeNO levels with measurements of personal PM (Delfino et al, 2006;Koenig et al, 2003Koenig et al, , 2005.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute effects due to the outdoor exposure to certain gases/ fumes and PM have not been sufficiently studied with regards to nasal symptoms. The few available studies inconsistently suggest an increase in rhinitis symptoms or consultations for allergic rhinitis during peaks of pollution (686)(687)(688). Pollution and meteorological factors are closely related to complaints of nonallergic, noninfectious perennial rhinitis patients (689).…”
Section: Pollutantsmentioning
confidence: 99%
“…15 In the case of pollen-sensitive individuals, increased symptoms have been seen for both particulate 16 and gaseous 17 traffic-derived pollutants compared with individuals who were not pollen sensitive. Steerenberg et al 18 report increased symptoms in response to air pollution for children sensitized to house dust mite allergen. Laboratory animal studies indicate that particulate traffic pollutants act as an adjuvant for allergens.…”
Section: Introductionmentioning
confidence: 99%